Bionic design for the heat sink inspired by phyllotactic pattern. (August 2021) - Lyu, Yushan; Yu, Haiyue; Hu, Yuheng; Shu, Qilin; Wang, Jun
A good heat dissipating condition will help give full play to the performance and reliability of electronic components and devices. To strengthen the heat dissipating performance, a novel bionic heat sink of pin fins has been designed. The configuration of cooling pin fins in this heat sink is based on phyllotaxis theory in biology. The bionic configuration of the cooling pin fins has better homogeneity and complementarity, which can form a reasonable air flow channel to improve its cooling efficiency. For testing and analyzing the performance of the bionic heat sink and the effects of the phyllotactic parameters on the heat dissipating, some contrast experiments have been conducted using thermal infrared imager. The results show that the bionic heat sink has better heat dissipating performance, which can make the surface temperature of the heat block lower by 14.7%. This paper will supply a new and effective solution to heat dissipation problem and has a certain contribution for the development of electrical and electronic industry.